Kreatywność genologiczna w podcaście Joanny Okuniewskiej "Ja i moje przyjaciółki idiotki" - badania wstępne = Genre creativity in Joanna Okuniewska`s podcast "Ja i moje przyjaciółki idiotki" [Me and my idiot friends] - preliminary research - Poroszewska, Dominika (Zielona Góra: Uniwersytet Zielonogórski, Instytut Filologii Polskiej)
The subject of this article is genre creativity, which involves expanding the conventional genre structures and introducing original elements into the text. The aim of the article is to preliminarily examine genre creativity in the context of a new media genre, the podcast, which, as a still poorly described phenomenon, lacks a clearly defined canonical model. The analysis focuses on the podcast ?Ja i moje przyjaciółki idiotki? and aims to determine which genre patterns are used in it. The study is based on the analysis of selected episodes of the podcast, in which the key features of blogs, stand-up, and letters to the editor have been identified.
Keywords: podcast; blog; stand-up; gatunek medialny; kreatywność genologiczna; list do redakcji; genre creativity; media genre; letter to the editor